Who are Anxious and Supposed to be “Jakarta One” ?: a Systemic Functional Linguistics Approach - Endras Setyadi Wicaksono; Djatmika Djatmika; Sumarlam Sumarlam (Lingua Cultura, 2018)
The purpose of this research was to know the structure of debate and the difference of usage of modulation by the candidates in the third session debate of Pilkada DKI Jakarta in 2017. The debate in a general election was a new medium in the campaign. This research revealed the form and meaning of dominated modulation used by the candidates by applying Systemic Functional Linguistics (SFL). This was a descriptive qualitative research using observation method in collecting the data. The source of data was a video of the third session debate of Pilkada DKI Jakarta in 2017. The data contained aspect of grammar and lexicon of the speech. Then, it was analyzed by using identity-method by Sudaryanto and content analysis suggested by Spradely. The result shows that there are two forms of modulation marker. It is modulation of inclination that is dominantly used by the first candidate and third candidate. Then, the second candidate dominantly uses modulation of obligation. The domination is a strategy of each candidate to defend and prioritize their programs for the next five years.